Peri-Implantitis Therapy Using Surgical Methods: A Systematic Review - Shiromani Wijesundara; Lavanya A. Sharma; Seyed Ebrahim Alavi; Ajay Sharma (Applied Sciences, 2023)
This study is a systematic review evaluating published literature on the effect of surgical treatments on peri-implantitis. Various databases were selected for the literature search on the topic. The considered primary clinical parameters were changes in probing pocket depth (PPD), bleeding on probing (BoP), radiographic bone change, plaque score, signs of infection, and implant loss. Five research studies comprising 20 or more sample sizes (patients) with minimal two-year follow-up after surgical treatment were selected, based on preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. In all five studies, PPD and BoP were significantly reduced compared to those before intervention. However, there was no significant variation in the patients treated with open flap debridement, citric acid decontamination, and subepithelial connective tissue graft. The highest reduction of BoP was recorded in the study utilizing regenerative surgical therapy, deproteinized bovine bone mineral containing 10% collagen, the derivative of enamel matrix, and doxycycline. According to the two–five-year follow-up of this systemic review, surgical treatment, including bone substitute material, showed clinical improvement in the reviewed studies, compared to that before intervention; however, there was no statistical significance in the clinical outcome of the selected studies.